(untitled) (International Journal of Studies in Nursing, 2019)
Background and aim: The internet is a worldwide area network that connects computer system throughout the world providing a variety of information and communication. Internet addiction is defined as any online-related, compulsive behavior which interferes with normal living and causes severe stress on family, friends, loved ones, and one’s work environment. Aim: This study assessed the internet usage and its addiction level among university students in a selected university in Ras Al Khaimah, United Arab Emirate. University students are highly predisposed to internet addiction which can affect their personal, family, educational, interactive and societal life. Study design: A cross-sectional design .The sample of the study consisted of 110 nursing students who were selected using convenient sample. Internet addiction test, internet usage questionnaire and student attitude scale were used as data collection instruments. Results: The findings showed that more than half (50.9%) of students were aged 21-<25 years, with more than two- fifth (45.5% of them being average online internet user. Less than two-third (62.7%) of students had favorable attitude towards internet usage. There is a positive correlation between internet addiction score and age of the study group with no statistically significant difference Conclusions: the study concluded that nursing students are average internet users, they have favorable attitude to internet use, with positive correlation between internet addiction score and age, though experiencing occasional problems. The use of social networking sites, especially by the young people, should be done sparingly so as not to provoke extreme behaviors and negative impact to their education performance and social life that can lead to destruction of the life of youths globally as revealed in this study Internet addiction is a serious problem among university students generally which indicates the need for more public attention and resources to develop effective prevention/intervention strategies.